On Death and Dying - Kübler-Ross, Elisabeth; Wessler, Stanford; Avioli, Louis V. (JAMA, 1972)
Dr. J. Russell Little, Chief, Division of Infectious Disease, the Jewish Hospital of St. Louis and Associate Professor of Medicine and Microbiology, Washington University School of Medicine: Our guest this morning is Elisabeth Kübler-Ross, MD. Dr. Ross has become something of a celebrity since the feature story inLifemagazine (Nov 21, 1969, p 36) concerning her and her work and the appearance of her recent book entitledOn Death and Dying.1The book provides a fascinating account of an experiment in teaching and therapy concerned with the emotional problems of seriously ill and dying patients. We have decided to dispense with the traditional case presentation today even though Dr. Ross could discuss any of our hospitalized patients with a terminal disease. Instead we shall turn over the entire hour to her discussion of her approach to the emotional problems of dying patients. Dr. Elisabeth Kübler-Ross, Medical Director, South